Preliminary Examining Judges in Indonesian Criminal Procedure Reform: Lessons from Australia’s Committal Hearings - Kukuh Dwi Kurniawan; Pujiyono Pujiyono; Irma Cahyaningtyas; Hasnan Bachtiar (Universitas Negeri Semarang, 2026)
This study examines Indonesia’s Preliminary Examining Judges (PEJ) and compares them with Australia’s committal hearings. We ask whether the PEJ can better protect human rights and prevent abuses of authority in Indonesia’s criminal justice system. Using a qualitative comparative approach, we analyze the PEJ in the 2012 Draft Criminal Procedure Code and Australia’s committal hearings, drawing on statutes, scholarly articles, and related regulations. We find that although the 2025 draft Code did not adopt the PEJ, the concept remains relevant and worth implementing. The Preliminary Examining Judge can improve the efficiency of the legal system by supervising investigations and ensuring only well-founded cases proceed to court. Operating at the pre-investigation stage with broad powers to direct inquiries and name suspects, the PEJ reflects the inquisitorial civil law tradition. By contrast, Australia’s committal hearings occur post-investigation and assess the evidentiary sufficiency for higher courts, consistent with the common-law adversarial model.